O Projecto ‘Estela’: primeiros resultados e perspectivas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Continuing the research and the promotion of archaeological heritage in Almodôvar area, the first two authors, with the scientific monitoring of the others, delineated the outline and took the responsibility for the project ESTELA, specifically dedicated to the Tartessian stelae and its archaeological context. Establishing that the ultimate aim of MESA (Museu da Escrita do Sudoeste, Almodôvar) is to relate the museum with the territory, we leaded an exploratory field survey in the summer of 2008, with the support of the municipality. With this experience it was possible to conclude that the find places identification of tmonuments already known it is also promising for the discovery of new ones, has led us to the discovery  of a new stela at Corte Pinheiro (Loulé).
Keywords: South-western writing; Iron Age; Estela Project; Almodôvar